THE EFFECT OF NON-PERFORMING FINANCING AND THIRD PARTY FUNDS ON THE PROFITABILITY THROUGH PS/RS AND PLS FINANCING - Salman, Kautsar Riza (International Journal of Islamic Banking and Finance Research, 2021)
This research is motivated by the phenomenon of increasing PS/RS and PLS financing and profitability at Islamic Commercial Banks (BUS) in Indonesia during the 2015-2019 period, and experiencing a decline from 2019 to 2020. PS/RS and PLS financing can use mudharabah and musharakah contract schemes. Mudharabah financing is based on profit sharing, while Musharaka is based on profit-loss sharing. This study aims to obtain empirical evidence regarding the effect of non-performing financing and third-party funds on profitability through PS/RS and PLS financing. The population used in this study were all Islamic Commercial Banks in Indonesia in the 2015-2020 period. The data analysis technique used is Partial Least Square with SmartPLS software version 3. The results of the study found a direct effect of non-performing financing on profitability. The results of the study did not find a direct effect of non-performing financing on PS/RS and PLS financing. In addition, third party funds do not have a direct effect on profit-sharing and profitability-based financing. The results also did not find an indirect effect of non-performing financing and third-party funds on profitability. JEL Classification Codes: A19, B10, B25, C10, C53.